2017
DOI: 10.1007/s00359-017-1209-1
|View full text |Cite
|
Sign up to set email alerts
|

Take time: odor coding capacity across sensory neurons increases over time in Drosophila

Abstract: Due to the highly efficient olfactory code, olfactory sensory systems are able to reliably encode enormous numbers of olfactory stimuli. The olfactory code consists of combinatorial activation patterns across sensory neurons, thus its capacity exceeds the number of involved classes of sensory neurons by a manifold. Activation patterns are not static but vary over time, caused by the temporally complex response dynamics of the individual sensory neuron responses. We systematically analyzed the temporal dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…What is the neural correlate of odor source segregation based on odorant onset asynchrony? In the antennal lobe, synchronous odorant mixtures often induce neural activity patterns that lack part of the component information (synthetic mixture representation) (Deisig et al., 2006, Krofczik et al., 2009, Meyer and Galizia, 2012, Münch et al., 2013, Münch and Galizia, 2017, Silbering and Galizia, 2007). In contrast, asynchronous mixtures induce spatiotemporal activity patterns across projection neurons that partly match those evoked by the individual odorants (analytic mixture representation), and this asynchrony-induced shift from synthetic to more analytic mixture processing could support odor source segregation (Broome et al., 2006, Saha et al., 2013, Stierle et al., 2013) (for a modeling approach see Nowotny et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…What is the neural correlate of odor source segregation based on odorant onset asynchrony? In the antennal lobe, synchronous odorant mixtures often induce neural activity patterns that lack part of the component information (synthetic mixture representation) (Deisig et al., 2006, Krofczik et al., 2009, Meyer and Galizia, 2012, Münch et al., 2013, Münch and Galizia, 2017, Silbering and Galizia, 2007). In contrast, asynchronous mixtures induce spatiotemporal activity patterns across projection neurons that partly match those evoked by the individual odorants (analytic mixture representation), and this asynchrony-induced shift from synthetic to more analytic mixture processing could support odor source segregation (Broome et al., 2006, Saha et al., 2013, Stierle et al., 2013) (for a modeling approach see Nowotny et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Active sniffing or odor sampling strategies also dramatically alter synaptic interactions in the olfactory bulb, the first central synaptic processing site for odor-elicited sensory input [ 9 , 10 ]. The temporal dynamics of olfactory receptor neuron (ORN) responses during odor sampling is a critical determinant of the information available to the olfactory bulb [ 11 13 ] or its analog, the antennal lobe in insects [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In natural environments, animals encounter different temporal patterns of odor stimuli. D. melanogaster ORNs show diversity in their temporal response dynamics (Hernandez-Nunez et al 2015;Mathew et al 2013;Montague et al 2011;Munch and Galizia 2017;Nagel and Wilson 2011). A systematic analysis of the temporal dynamics of ORNs revealed that the response dynamics of an ORN depend on the combination of sensory neuron and odor (Munch and Galizia 2017).…”
Section: Section 3: Implications Of Neuronal Diversity For Circuit Functionmentioning
confidence: 99%